Valorization of food waste via surface modification by loading Fe to obtain an adsorbent for Cr(V) removal - Seo, Eun Jin; Lee, Chang Gu; Park, Seong Jik (Desalination and Water Treatment, 2024)
Fe-loaded food waste (Fe-FW) utilization is an environmentally friendly and effective approach for eliminating Cr(VI). FW was blended with iron to enhance its adsorption capacity for Cr(VI) removal from aqueous solutions. The Fe-FW was characterized by examining its elemental composition, specific surface area, morphological properties, functional groups, and zeta potential. The Cr(VI) adsorption properties of Fe-FW were examined using batch experiments. Cr(VI) adsorption onto the Fe-FW occurred according to the pseudo-second-order model at various contact times, indicating that the Cr(VI) adsorption rate was primarily constrained by chemical adsorption. The coefficient of determination was more suitable for the Langmuir model than for the Freundlich model. Fe-FW achieved a maximum Cr(VI) adsorption capacity of 100.6 mg/g, comparable to that of adsorbents investigated in other studies. Thermodynamic experiments indicated that Cr(VI) adsorption onto Fe-FW occurs spontaneously, is endothermic, and follows a physical adsorption mechanism. As the solution pH increased from 3 to 11, the amount of Cr(VI) adsorbed decreased considerably (from 39.6 mg/g to 2.5 mg/g). HPO42- had a stronger negative effect on Cr(VI) adsorption compared to SO42-, NO3-, and HCO3-. HCl effectively facilitated the regeneration of Fe-FW. This study confirmed that FW treated with Fe is an effective adsorbent for improving Cr(VI) removal.
Keywords: Adsorption; Cr(VI) removal; Food waste; Iron loading; Regeneration